BEOWULF AS A REFLECTION OF ANGLO-SAXON CULTURE - Eldorbek Erkin og’li Khamitov,; Nurymbetova Zumrad Ruslanovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
The  epic  Beowulf  provides  a  rich  representation  of  Anglo-Saxon  culture, offering deep insight into the social norms, moral principles, and political structures of early  medieval England. This paper explores how the story, its characters, and the heroic  ideals  showcased  in  Beowulf  reflect  the  customs,  beliefs,  and  societal organization of the Anglo-Saxon era. Key themes such as bravery, loyalty, and honor are central to the poem, reflecting the core values of a warrior-centric society. The text also highlights the tribal and feudal systems, focusing on the relationships between lords and thanes, the importance of family ties, and the responsibilities that governed communal life.